Stability Results for Set Differential Equations Involving Causal Operators with Memory (European Journal of Pure and Applied Mathematics, 2012)
In this paper we study the stability concepts for set differential equations involving causalÂ operators with memory by considering initial functions as a Hukuhara difference of two functions. ThisÂ will enable to obtain results parallel to ordinary differential equations with delay.